KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK DALAM PEMECAHAN SOAL CERITA MATEMATIKA MATERI OPERASI HITUNG BILANGAN KELAS IV SEKOLAH DASAR - Nurmadani, Kurnia; Sastrawati, Eka; Syarif, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the This study aims to describe the creative thinking ability of elementary school students in solving mathematical word problems on arithmetic operations in fourth grade. The research employed a qualitative approach with a case study design. The subjects were 28 fourth-grade students of SDN 70/IV Kota Jambi. Data were collected through tests, observations, and interviews, using instruments validated by experts. The analysis focused on four indicators of creative thinking: fluency, flexibility, originality, and elaboration. The results show that students’ creative thinking ability is generally low. In terms of fluency, only a small number of students were able to generate more than one solution, while most relied on a single common method. Regarding flexibility, students with high ability could switch strategies when facing difficulties, whereas others tended to stick to one method. Originality emerged as the weakest aspect, with most students providing uniform answers based on the teacher’s example, and only a few showing unique or different ideas. For elaboration, the majority of students wrote only the final answer without detailing the solution steps, while only those in the high category could explain their process systematically. These findings indicate that although a small number of students demonstrated high creative thinking ability, the majority still performed at a low level across the four indicators. This study implies the need for learning strategies that emphasize the process of creative thinking, provide space for students to explore new ideas, try alternative strategies, and practice explaining their solutions systematically.